Comparison of Postoperative Outcomes between Leadless and Conventional Transvenous Pacemakers Implantation: An Up-to-Date Meta-analysis - Huimiao Dai; Hao Liu; Chuncheng Gao; Jing Han; Jun Meng; Pengyun Liu; Mingming Zhang; Dongdong Li; Wangang Guo (Reviews in Cardiovascular Medicine, 2024)
Background: Leadless cardiac pacemakers (LCPs) are emerging as viable alternatives to conventional transvenous pacemakers (TVPs). This study aimed to systematically compare the postoperative outcomes of LCPs and TVPs based on available published studies. Methods: We conducted a systematic review and meta-analysis of literature comparing outcomes from LCP and TVP implantations. Data analysis was performed using Stata/MP 17.0. The evaluated endpoints included pericardial effusion or perforation, puncture site events, infective endocarditis, lead or device dislodgement, pocket-related complications, tricuspid regurgitation or dysfunction, any infection, increased right ventricle (RV) pacing threshold, embolism, and thrombosis. Aggregated odds ratios (OR) and 95% confidence intervals (CI) were determined. Sensitivity analyses were conducted for heterogeneity if I2 was >50% or p < 0.01, otherwise, the random-effects model was chosen. Publication bias was analyzed if the number studies exceeded ten. Results: The meta-analysis included 24 observational studies with 78,938 patients, comprising 24,191 with LCP implantation and 54,747 with TVP implantation. The results indicated a significantly lower incidence of lead or device dislodgment (OR = 3.32, 95% CI: 1.91–5.77, p < 0.01), infective endocarditis (OR = 3.62, 95% CI: 3.10–4.24, p < 0.01), and infection (OR = 3.93, 95% CI: 1.67–9.24, p < 0.01) in the LCP group compared to the TVP group. In contrast, incidences of puncture site complications (OR = 0.24, 95% CI: 0.19–0.32, p < 0.01) and pericardial effusion or perforation (OR = 0.33, 95% CI: 0.28–0.39, p < 0.01) were significantly higher in the LCP group. Conclusions: Compared with TVP, LCP implantation is associated with a lower risk of infective endocarditis, lead or device dislodgment, infections, and pocket-related complications. However, LCP implantation carries a higher risk of puncture site complications and pericardial effusion or perforation. These findings underscore the need for careful consideration of patient-specific factors when choosing between LCP and TVP implantation. The PROSPERO Registration: https://www.crd.york.ac.uk/prospero/ (CRD42023453145).